Sodium butyrate ameliorates gut dysfunction and motor deficits in a mouse model of Parkinson’s disease by regulating gut microbiota - Zhang, Yi; Xu, Shaoqing; Qian, Yiwei; Mo, Chengjun; Ai, Penghui; Yang, Xiaodong; Xiao, Qin (Frontiers in Aging Neuroscience, 2023)
Abstract Background: A growing body of evidence showed that gut microbiota dysbiosis might be associated with the pathogenesis of Parkinson’s disease (PD). Microbiota-targeted interventions could play a protective role in PD by regulating the gut microbiota-gut-brain axis. Sodium butyrate (NaB) could improve gut microbiota dysbiosis in PD and other neuropsychiatric disorders. However, the potential mechanism associated with the complex interaction between NaB and gut microbiota-gut-brain communication in PD needs further investigation. Methods: C57BL/6 mice were subjected to a rotenone-induced PD model and were treated intragastrically with NaB for 4 weeks. The gut function and motor function were evaluated. The α-synuclein expression in colon and substantia nigra were detected by western blotting. Tyrosine hydroxylase (TH)-positive neurons in substantia nigra were measured by immunofluorescence. Moreover, gut microbiota composition was analyzed by 16S rRNA sequencing. Fecal short chain fatty acids (SCFAs) levels were determined by liquid chromatography tandem mass spectrometry (LC-MS). The levels of glucagon like peptide-1 (GLP-1) in tissues and serum were evaluated using enzyme-linked immunosorbent assay (ELISA). Results: NaB ameliorated gut dysfunction and motor deficits in rotenone-induced mice. Meanwhile, NaB protected against rotenone-induced α-synuclein expression in colon and substantia nigra, and prevented the loss of TH-positive neurons. In addition, NaB could remodel gut microbiota composition, and regulate gut SCFAs metabolism, and restore GLP-1 levels in colon, serum, and substantia nigra in PD mice. Conclusion: NaB could ameliorate gut dysfunction and motor deficits in rotenone-induced PD mice, and the mechanism might be associated with the regulation of gut microbiota dysbiosis.